PENENTUAN EMISI RADIASI TERMAL PADA BERBAGAI JENIS BAHAN - Mousa, Almahdi; Purwaningsih, Sri; Ziarah, Hikmah; Ambarwati, Ria; Fardela, Romacos (EduFisika: Jurnal Pendidikan Fisika, 2023)
The research aims to measure and compare the amount of thermal radiation emitted by various materials with different colors and textures, and to calculate the emissivity of each material. Experiments were carried out using four surface variations of the cube. The results show that the black surface of the Leslie cube emitted the most thermal radiation, followed by the dull, shiny, and white surfaces. The average value of thermal radiation output for each surface was 3.4 mV for black material, 1.6 mV for white material, 2.4 mV for shiny colored materials, and 2.8 mV for dull colored materials. The amount of power obtained for each surface was 1.9 x 10-8 Watts, 0.87 x 10-8 Watts, 1.3 x 10-8 Watts, and 1.6 x 10-8 Watts, respectively. The emissivity of each material, which is the ratio of the thermal radiation emitted by the material to that of a black body at the same temperature, was 1, 0.458, 0.684, and 0.842, respectively. Based on the sensor output value, it can be concluded that black cloth is the most effective material in transmitting thermal radiation energy compared to glass, cardboard, and styrofoam. The research also provides empirical data and calculations of the thermal radiation and emissivity of different materials, which can be used for further analysis and applications. The research contributes to the literature on physics education and thermal radiation by demonstrating a practical and engaging way of teaching and learning the concept of thermal radiation using a Leslie cube.